Structural Aspects of DNA Repair and Recombination in Crop Improvement - Verma, Prabha; Tandon, Reetika; Yadav, Gitanjali; Gaur, Vineet (Frontiers in Genetics, 2020)
The adverse effects of global climate change combined with an exponentially increasing human population have put substantial constraints on agriculture, accelerating efforts towards ensuring food security for a sustainable future. Conventional plant breeding and modern technologies have led to the creation of plants with better traits and higher productivity. Most crop improvement approaches (conventional breeding, genome modification, and gene editing) primarily rely on DNA repair and recombination (DRR). Studying plant DRR can provide insights into designing new strategies or improvising the present techniques for crop improvement. Even though plants have evolved specialized DRR mechanisms compared to other eukaryotes, most of our insights about plant-DRRs remain rooted in studies conducted in animals. DRR mechanisms in plants include direct repair, nucleotide excision repair (NER), base excision repair (BER), mismatch repair (MMR), non-homologous end joining (NHEJ) and homologous recombination (HR). Although each DRR pathway act on specific DNA damage, there is crosstalk between these. Considering the importance of DRR pathways as a tool in crop improvement, this review focuses on a general description of each DRR pathway, emphasizing on the structural aspects of key DRR proteins. The review highlights the gaps in our understanding and the importance of studying plant DRR in the context of crop improvement.